Effect of the COVID-19-induced lockdown on nutrition, health and lifestyle patterns among adults in Zimbabwe. Issue 2 (12th September 2020) - Matsungo, Tonderayi Mathew; Chopera, Prosper
Abstract : Background: The COVID-19 is a global public health emergency resulting in lockdowns, associated diet and lifestyle changes and constrained public health delivery. Objective: To investigate the impacts of the COVID-19-induced lockdown in Zimbabwe on nutrition, physical activity, alcohol consumption and smoking among Zimbabwean population aged ≥18 years. Methods: A cross-sectional online survey was conducted using a structured questionnaire to collect information on demographics (age, gender, place of residence, current employment), food system dimensions, diet and physical activity patterns, stress and anxiety, body image perceptions, lifestyle behaviours like smoking, alcohol intake, screen time and ease of access to health services. Results The participants (n=507) were mostly women (63.0%) between the ages of 31 and 40 years (48.1%) and had tertiary education (91.3%). The lockdown resulted in increase in food prices (94.8%) and decrease in availability of nutritious foods (64%). Most (62.5%) of the participants reported a reduction in their physical activity levels. The prevalence of generalised anxiety disorder (GAD) was 40.4% and mostly affecting woman (63.5%, p=0.909), 31–40 years age group (49.6%, p=0.886). Based on the Body Mass Index-based Silhouette Matching Test (BMI-SMT) 44.5% gained weight, 24.3% lost weight and 31.2% did not have weight change. The paired samples t-test showed that there was a significant increase in perceived body weight (p<0.001). More than half (59.6%) reported having difficulties accessing medicinal drugs and 37.8% growth monitoring services. Conclusions: The lockdown period was associated with increase in food prices, decrease in dietary diversification, elevated GAD symptoms, disrupted diet and consumption patterns. There were low levels of physical activity and perceived weight gained during the lockdown period, thus increasing the risk of overweight and obesity. Further studies incorporating participants of different socioeconomic status are warranted to get more conclusive results.